HIGHER EDUCATION IS AN IMPORTANT CONDITION FOR ESTABLISHING A NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
In article pressing questions of the further development of system of higher education in the conditions of a new stage of development are considered. The author investigates problems of reforming of higher education in a context of innovative development of the country and as important factor of maintenance of a sustainable development of a society. In work аre considered communication of this point in question with introduction of innovative methods in system of preparation of modern shots.The author investigated problems of development of the higher school in new conditions as important factor in a society sustainable development. Attempt to connect modern problems of perfection of system of the higher school with реформационным processes in the country is made.